2018
DOI: 10.3390/su10124349
|View full text |Cite
|
Sign up to set email alerts
|

Towards Economic Corporate Sustainability in Reporting: What Does Earnings Management around Equity Offerings Mean for Long-Term Performance?

Abstract: Companies are very important contributors to the long-term sustainable wealth of economies and society. Public companies are likely to be especially important for economic, environmental, and social development. That is why we focus on initial public offerings (IPO). Responsible external reporting relates to the long-term value of companies and influences perceptions of value by stakeholders. This study contributes to the literature not only because it concentrates on earning quality in terms of going public, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 90 publications
2
40
0
Order By: Relevance
“…Their findings show that aggressive managers experience 20 percent lower stock returns than conservative managers. Recently, Lizińska and Czapiewski [9] found similar results, showing that positive and significant discretionary accruals in the IPO year are negatively correlated with subsequent long-term market value. Rangan [10] used seasoned equity offerings and examines earnings management around offerings.…”
Section: Prior Research On Sustainable Earningsmentioning
confidence: 60%
“…Their findings show that aggressive managers experience 20 percent lower stock returns than conservative managers. Recently, Lizińska and Czapiewski [9] found similar results, showing that positive and significant discretionary accruals in the IPO year are negatively correlated with subsequent long-term market value. Rangan [10] used seasoned equity offerings and examines earnings management around offerings.…”
Section: Prior Research On Sustainable Earningsmentioning
confidence: 60%
“…Public companies can be especially important contributors to the long-term sustainable wealth of economies and society [30]. This study examined the characteristics of companies ahead of delisting in the KOSDAQ market and in conservative accounting.…”
Section: Discussionmentioning
confidence: 99%
“…This includes upward earnings management. In this context, existing research has shown that companies about to be listed tend to use information asymmetry by engaging in upward earnings management [11,13,[19][20][21][22][23]. Therefore, investors believe that any other information they can secure before making investment decisions only based on public financial information acts as an incentive for them to reflect on their own decisions [3,24,25].…”
Section: Prior Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Therefore, it can be said that underwriters participating in new listing processes control the upward earnings management and inadequate or inappropriate disclosure of newly listed companies [5,13,23,[42][43][44]. In this respect, it is believed that underwriters play an important role in helping both newly listed companies and related stakeholders through decreasing the information asymmetry between them.…”
Section: Prior Literature and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation